Mapping the Maricopa Agricultural Center Using a Geographic Information System - Regan, John J. (Arizona-Nevada Academy of Science, 1989)
From the Proceedings of the 1989 Meetings of the Arizona Section - American Water Resources Association and the Hydrology Section - Arizona-Nevada Academy of Science - April 15, 1989, University of Nevada, Las Vegas, Nevada